2015
DOI: 10.1177/1091581815589766
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Exposure and Endothelial Dysfunction

Abstract: Vascular endothelium plays a vital role in the organization and function of the blood vessel and maintains homeostasis of the circulatory system and normal arterial function. Functional disruption of the endothelium is recognized as the beginning event that triggers the development of consequent cardiovascular disease (CVD) including atherosclerosis and coronary heart disease. There is a growing data associating mercury exposure with endothelial dysfunction and higher risk of CVD. This review explores and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…A large number of studies have well identified and characterised the negative effects of mercury on organism health. It was discovered that mercury can increase oxidative stress, reduced oxidative defence, thrombosis, mitochondrial dysfunction, hyperlipidaemia, inflammation and vascular/endothelial dysfunction [36,37], all of which can contribute to cardiovascular disease development and progression by initiating the development of atherosclerosis. It was demonstrated that endothelial function can be improved by the treatment with atorvastatin, in the case of patients with hyperlipidaemia, while the measurement of intima media thickness (IMT) together with the determination of high sensitive C reactive protein (hsCRP) can have a predicting value for future CAD events [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have well identified and characterised the negative effects of mercury on organism health. It was discovered that mercury can increase oxidative stress, reduced oxidative defence, thrombosis, mitochondrial dysfunction, hyperlipidaemia, inflammation and vascular/endothelial dysfunction [36,37], all of which can contribute to cardiovascular disease development and progression by initiating the development of atherosclerosis. It was demonstrated that endothelial function can be improved by the treatment with atorvastatin, in the case of patients with hyperlipidaemia, while the measurement of intima media thickness (IMT) together with the determination of high sensitive C reactive protein (hsCRP) can have a predicting value for future CAD events [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…Ros has been shown to have multiple effects besides inhibition of HMG-CoA reductase, such as increasing nitric oxide synthase expression (Huang et al, 2012;Omanwar and Fahim, 2015), decreasing ROS-mediated stress (Mahalwar and Khanna, 2013), and exerting anti-inflammatory actions (Srivastava et al, 2009). However, its effect on ER stress has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells are vulnerable to oxidative stress, which when increased by MeHg causes endothelial dysfunction, leading to the development of atherosclerosis, thrombosis, vasospasm, and inflammation [37,38]. Consequently, it is associated with risk of atherothrombotic diseases, such as hypertension, cerebrovascular diseases, renal dysfunction, and acute myocardial infarction [39,40,41,42,43].…”
Section: Systemic Vascular Effects Of Mehg Intoxicationmentioning
confidence: 99%